Analysis of the state and development opportunities of hospitality industry on the example of Sergiivka resort (Ukraine) - Lebedenko, Tetiana; Nikitchina, Tatiana; Shunko, Hanna; Kozhevnikova, Viktoriia (Technology audit and production reserves, 2021)
The object of research is the hospitality industry in the context of the recovery of the industry and the fight against the effects of the pandemic. The development of domestic tourism and local destinations is considered one of the most effective ways to restore the industry. At the same time, experts recommended that the greatest attention be paid to health tourism and ecotourism. The analysis of the potential of the institutions of the sanatorium-resort direction and the study of the problems of the development of the sphere of hospitality were considered on the example of the resort of Sergiivka, Odessa region of Ukraine. In the course of the study of the state of the resort base of the region, methods of comparative analysis, generalization and systematization of information about the natural-climatic, social and other resources of the region, the state of hospitality institutions and sanatorium-resort complexes were used. Strengths and challenges were identified that hinder their effective use. So, Sergiivka is considered one of the largest seaside resorts in the region, which is located in the beach area and has a good climate, environmental friendliness and significant balneological resources. However, the problematic issues are the underdeveloped infrastructure of the resort, the level of service that requires improvement, the quality of the room stock, the work of restaurants and the organization of recreation. The studies carried out indicate the importance of developing measures for the reconstruction of most powerful establishments of the hotel and restaurant and sanatorium business. The need to create comfortable living conditions in accordance with world standards, to improve the range and quality of services, in particular, to organize leisure for adults and children, was noted. One of the recommended directions is to expand the range of services in the SPA and Wellness directions, which will allow more efficient use of the healing, restorative and health-improving resources of the balneological resort. Organic production and ecotransformation are also considered priority innovative areas of development. It is promising to use the agro-industrial potential of the region for the production of organic, environmentally friendly food products from local raw materials, as well as the introduction of more environmentally friendly and resource-efficient technologies.